Design and Construction of a 500–800 MHz Square Spiral Dipole Microstrip Antenna Structure - Setiawan, Arif Milando (Universitas Nurul Jadid, 2024)
An antenna can be used to detect an object. The dimensions of the antenna also affect the working frequency, the smaller dimensions, the higher the working frequency and the closer the antenna range to radiate waves. Therefore, a microstrip antenna with a small dimension size is needed, but the antenna radiation distance capability for radar systems still needs to be reduced. A microstrip dipole antenna with a spiral shape, measuring 5 cm, was meticulously designed and fabricated. The square dipole antenna, featuring an optimal design with the arm structure rotated in a clockwise direction, achieved an impressive return loss of -27.54dB with a VSWR of 1.83. The engineering refinement of the antenna design involved the addition of a square shape, which led to a significant and impressive improvement in performance. The second spiral antenna, operating at a frequency of 805MHz with an impressive bandwidth of 57MHz, exhibited a remarkable return loss of -30.83dB and a VSWR of 1.07.